The impact of reader fatigue on the accuracy of capsule endoscopy interpretation. Issue 8 (August 2021) - Beg, Sabina; Card, Tim; Sidhu, Reena; Wronska, Ewa; Ragunath, Krish; ,; Ching, Hey-Long; Koulaouzidis, Anastasios; Yung, Diana; Panter, Simon; Mcalindon, Mark; Johnson, Matthew; et al.
Abstract: Background and aims: Capsule endoscopy (CE) interpretation requires the review of many thousands of images, with lesions often limited to just a few frames. In this study we aim to determine whether lesion detection declines according to the number of capsule videos read. Methods: 32 participants, 16 of which were novices (NR) and 16 experienced (ER) capsule readers took part in this prospective evaluation study. Participants read six capsule cases with a variety of lesions, in a randomly assigned order during a single sitting. Psychomotor Vigilance Tests and Fatigue Scores were recorded prior to commencing and then after every two capsules read. Changes in lesion detection and measures of fatigue were assessed across the duration of the study. Results: Mean agreement with the predefined lesions was 48.3% (SD:16.1), and 21.3% (SD:15.1) for the experienced and novice readers respectively. Lesion detection declined amongst experienced reader after the first study ( p  = 0.01), but remained stable after subsequent capsules read, while NR accuracy was unaffected by capsule numbers read. Objective measures of fatigue did not correlate with reading accuracy. Conclusion: This study demonstrates that reader accuracy declines after reading just one capsule study. Subjective and objective measures of fatigue were not sufficient to predict the onset of the effects of fatigue.